Healthcare professionals' perceptions of learning communication in the healthcare workplace: an Australian interview study. Issue 2 (7th February 2019) - Denniston, Charlotte; Molloy, Elizabeth K; Ting, Chee Yan; Lin, Qi Fei; Rees, Charlotte E
Abstract : Objectives: The literature focuses on teaching communication skills in the 'classroom', with less focus on how such skills are informally learnt in the healthcare workplace. We grouped healthcare work based on the cure:care continuum to explore communication approaches based on work activities. This study asks: 1) How do healthcare professionals believe they learn communication in the workplace? 2) What are the differences (if any) across the 'type of work' as represented by the cure:care continuum? Design: This qualitative study used semi-structured individual interviews. Setting: Community care and acute hospitals in Australia (Victoria and New South Wales). Participants: Twenty qualified healthcare professionals (medicine n=4, nursing n=3, allied health n=13) from various clinical specialties (eg, acute, rehabilitation, surgery, palliative care) participated. Methods: Data were analysed using framework analysis, which involved the development of a thematic coding framework. Findings were mapped to participants' descriptions of work using the cure:care continuum. Results: Three themes were identified that varied across the cure:care continuum: professional discourse—tying communication approaches to work activities; personal identities—the influence of personal identities on healthcare communication and role modelling—the influence of others in the socially bound context of healthcare work. Conclusions: This study highlights the influence of professional, personal and social factors on the learning of healthcare communication in the workplace. Our study illuminates differences in communication practice related to work activities, as conceptualised by the cure:care continuum. The results call for further examination of the 'nature' of work activities and the concomitant influence on developing healthcare communication.